Domain I of β2GPI is capable of blocking serum IgA antiphospholipid antibodies binding in vitro: an effect enhanced by PEGylation. (June 2019) - Albay, A; Artim-Esen, B; Pericleous, C; Wincup, C; Giles, I; Rahman, A; McDonnell, T
Objectives: This study aims to inhibit antiphospholipid syndrome (APS) serum derived IgA anti-beta-2-glycoprotein I (aβ2GPI) binding using Domain I (DI). Methods: Serum from 13 APS patients was tested for IgA aβ2GPI and Anti-Domain I. Whole IgA was purified by peptide M affinity chromatography from positive serum samples. Serum was tested for IgA aβ2GPI binding in the presence and absence of either DI or of two biochemically modified variants containing either 20 kDa of poly(ethylene glycol) (PEG) or 40 kDa of PEG. Results: Significant inhibition with DI was possible with average inhibition of 23% ( N  = 13). Further inhibitions using 20 kDa PEG-DI and 40 kDa PEG-DI variants showed significant inhibition ( p  = 0.0001) with both the 40 kDa PEG-DI and 20 kDa PEG-DI variants showing increased inhibition compared with DI alone ( p  = 0.0001 and p  = 0.001, n  = 10). Conclusions: Inhibition of IgA aβ2GPI by DI is possible and can be enhanced by biochemical modification in a subset of patients.